Ferroelectric and dielectric behaviour of Bi0.92La0.08FeO3 multiferroic thin films prepared by soft chemistry route - Simoes, Alexandre Z.; Cavalcante, Laecio Santos; Riccardi, Carla Santos; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer, 2007)
Bi0.92La0.08FeO3 (BLFO) thin films were grown on platine substrates by the soft chemical route. Ferroelectric and dielectric behaviors of BLFO films deposited by spin-coating technique and annealed at 773 K for 2 h in air atmosphere were explained. BLFO thin films obtained presents a rhombohedral structure. The BLFO films present dielectric and ferroelectric behaviors with dielectric permittivity and dielectric loss of approximately 81 and 0.0144 at 1 kHz. The Au/BLFO/Pt capacitor shows a hysteresis loop with remnant polarization of 20.6 mu C/cm(2) and coercive field of 53.88 kV/cm. The polarization switching and the fatigue behavior of the BLFO films were significantly enhanced.
Keywords: ferroelectrics; dielectric; microstructure; BiFeO3; thin films